Integration of soft skills in the teaching of technical courses: an exploratory study of a private university / Hairuzila Idrus - Idrus, Hairuzila (Institute of Graduate Studies, UiTM, 2013)
Institutions of higher education have been pressed by the industry practitioners to produce quality graduates who are ready to compete in the competitive job market locally and globally. Graduates, especially in the technical field are perceived as strong in their technical skills but are lacking in non-technical or soft skills that would enable them to use their technical skills most effectively. Thus, it is vital to integrate the soft skills in the teaching and learning process especially in the realm of engineering in order to further enhance the students’ ability in non-technical. The expected outcome would be the production of well-rounded engineering graduates with first class mentality as envisioned by the government. This empirical study attempts to craft a richer description and understanding of how soft skills are integrated into the teaching and learning of the formal curriculum focusing on technical courses at a private university in Malaysia. The study was based on both quantitative method, utilizing questionnaire survey and qualitative methods through document analysis and focus group interviews. Perspectives from both the educators and students were sought…